3x+y-2z=9

Simple and best practice solution for 3x+y-2z=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+y-2z=9 equation:


Simplifying
3x + y + -2z = 9

Solving
3x + y + -2z = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1y' to each side of the equation.
3x + y + -1y + -2z = 9 + -1y

Combine like terms: y + -1y = 0
3x + 0 + -2z = 9 + -1y
3x + -2z = 9 + -1y

Add '2z' to each side of the equation.
3x + -2z + 2z = 9 + -1y + 2z

Combine like terms: -2z + 2z = 0
3x + 0 = 9 + -1y + 2z
3x = 9 + -1y + 2z

Divide each side by '3'.
x = 3 + -0.3333333333y + 0.6666666667z

Simplifying
x = 3 + -0.3333333333y + 0.6666666667z

See similar equations:

| 65=6x+7y | | 1.4+0.3=1.7 | | -4(5y-5)-y=-2(y-4) | | .7x-1.5=.4x+1.2 | | 6(r+7)=60 | | 5/9=x-1/12 | | 2x-4(x-2)=-4+5x-23 | | ln(x-7)=ln(x+5) | | 16x(5-x)=30 | | x-x^2=56 | | -9=-11+6 | | 67=11+7x | | 26+6s=74 | | -3(x+2)-4=-1 | | (14+a)+14= | | -2z+-4=6 | | 14x-12=36+x^2 | | -3(2y-3)-y=-2(y-3) | | 10+(3+b)= | | 8x-4x+3=8 | | 3z/7-7=4 | | -37=8x+3 | | 6=-2r-2 | | 6.5x=24 | | 17*(ab)= | | p(x)=3x^4-2x^2-x+2 | | 4y-4+4y-8= | | w/5-3=4 | | 2x+265=1000 | | 4+3w=10 | | 7i=12 | | 23-2b=7 |

Equations solver categories